PENGARUH KUALITAS SUMBER DAYA MANUSIA, KINERJA INDIVIDU, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP RELEVANSI LAPORAN KEUANGAN INSTANSI PEMERINTAH (Studi Pada Pemerintah Kota Yogyakarta) - Abdul Rauf (JURNAL EKOBIS DEWANTARA, 2018)
This research purpose is for testing effects from quality of human resources,, individual performance, and utillization technology of information in simultaneous nor partial toward relevance government financial report to Yogyakarta government. Population from this research is employee/staff that do fungtion of accountancy at Yogyakarta mayor office.sample of this research determined with using purposive sampling technique with criteria that we have, with the result 50 questionnaire which is fulfill the condition as a sample. Kind of data that we use is primary data. From the questionnaire that spread 8 (eight) SKPD are social agency, coperation agency, midle micro labor,employeed teritory agency, BAPPEDA, cultural agency, tourism agency, and secretariat DPRD central, and all of them fill with complete. Analysis technique data that used is using regression double linier method. Result regression test, indicatin if the quality of human resource, individual performance, and utillization technology of information in simultaneous has influential significantly positive into the relevance government financial report. In partial, the quality of human resource, and individual performance, not influential significantly toward relevance of government financial report and utillization technology of information influent signifanctly positive toward relevance financial report. the influence of independent variable looked by coefficient determination value (R2) is 0,384, that had meaning the quality of human resource individual performance, and utillization technology of information, give positive effect toward relevance of government financial report as much 38,5% while the 61,6% influence by another variable beside this research. Keyword : Quality Of Human Resource, Individual Performance, Utillization Technology Of Information And Relevance Government Financial Report.